Energy Intake Is Highly Associated with Handgrip Strength in Community-Dwelling Elderly Adults. Issue 5 (9th March 2021) - Doyev, Ronit; Axelrod, Rachel; Keinan-Boker, Lital; Shimony, Tal; Goldsmith, Rebecca; Nitsan, Lesley; Dichtiar, Rita; Sinai, Tali
ABSTRACT: Background: Handgrip strength (HGS) is used to assess muscle strength, which is an important indicator of health status in older adults. Objective: We evaluated associations of demographic, anthropometric, clinical, and nutritional factors with muscle strength in community-dwelling elderly adults. Methods: This population-based cross-sectional study employed the 2014–2015 Israeli Health and Nutrition Survey in the Elderly ( n  = 1039, age ≥65 y, 46.7% males, 9.9% Arabs). Trained personnel performed face-to-face interviews that focused on health and nutrition status, as well as anthropometric measurements and examinations. HGS was measured in the dominant hand 3 times using a digital grip strength dynamometer; the highest result was reported. Dietary intake data were collected using single-day 24-h recall. Multivariable logistic regressions were used to explore factors associated with low HGS (<27 kg for men and <16 kg for women). Results: HGS measurements were completed by 704 participants. Following adjustment for several factors, higher prevalence of low HGS was significantly associated with age (OR: 1.14; 95% CI: 1.11, 1.18), whereas decreased prevalence was associated with higher levels of education (OR: 0.55; 95% CI: 0.32, 0.94) and meeting physical activity recommendations (OR: 0.53; 95% CI: 0.31, 0.88); P  < 0.05 for all. Incremental increases of 100 kcal/d in energy intake and of 1 cm in midarm circumference were associated with decreased prevalence of low HGS (OR: 0.95; 95% CI: 0.91, 0.99 and OR: 0.91; 95% CI: 0.85, 0.97, respectively; P  < 0.01 for both). Associations were not found of low HGS with ethnicity, comorbidity, BMI, smoking, or alcohol consumption or with protein, carbohydrate, or fat intakes. Conclusion: Energy intake, physical activity, midarm circumference, and education are associated with HGS in elderly Israeli adults. Further cohort studies are necessary to assess possible causal relations between these factors and HGS. Modifiable factors should be targeted in planning public health strategies for promoting a healthy aging population.